Bahasa INGGRIS: bahasa inggris - Adha, Ikhsan Fauzi; Alim Putri, Rahma Novita; Adzka, Nadia (Universitas 17 Agustus 1945 Surabaya, 2026)
Competition in the private higher education sector and the shift in Generation Z's digital preferences demand innovative recruitment strategies that go beyond conventional social media. This study aims to analyze the marketing communication strategy of Mercu Buana University Yogyakarta (UMBY) through live streaming activities on TikTok and Instagram platforms using the Customer Engagement Theory framework. The research method used is a qualitative case study approach, involving in-depth interviews with policymakers, operational staff, and live streaming hosts, as well as participant observation over four months at UMBY Campus 3. The results show that the routine implementation of live streaming effectively activates the cognitive, emotional, behavioral, and social dimensions of the audience, with technology as a determining dimension that mediates these interactions. This synchronous interaction successfully reduces uncertainty for prospective students through real-time registration guidance. This strategy has a significant impact on increasing the number of registrants by 15% in the special wave of 2025. This research provides a theoretical contribution in the formulation of the